Analysis of the Role of the State in Protecting Child Rights in Accordance with the Constitution of the Republic Democratic of Timor-Leste - Lourenco de Deus Mau Lulo; Maria Soares de Araujo (International Journal of Educational and Life Sciences, 2023)
The Democratic Republic of Timor-Leste, as a Democratic State of Law, as set out in the RDTL Constitution, article 1 (1) states that the Democratic Republic of Timor-Leste, the rule of law, the Democratic, the sovereign, the unitary, the self-governing and the self-governing of the will of the people and in respect for the dignity of each person. This is the fundamental principle of citizens under the concept of the rule of law itself, therefore, the state of Timor-Leste has a full obligation to protect the human rights of its citizens, including children, in accordance with the objectives set out in Article 6 (1) (b) of the RDTL Constitution, to guarantee and promote the fundamental rights and freedoms of its citizens, and respect the principle of the state in relation to democratic rights. In view of the reality of the above, the writer has created three aspects that are essential in this research, namely; The first legal aspect; the writer sees and analyser in more detail the legal system in Timor-Leste, which is mostly an alternative for the state to adapt and exist from the legal framework in Timor-Leste. Second, Sociology; the writer focuses on social problems that always involve children in any activity, such as political activities, juvinil conflicts, education and workers, taking into account these situations, the writer is also concerned about the current situation in Timor-Leste. Third Aspect Theory, the writer focused on the policy of law in the legal system of Timor-Leste .